Book Review: Gontor's Waqf, Philosophy and Manifestation - Rahman, Fathan Aulia (SMART Insight, 2024)
The book Wakaf Gontor: Philosophy and Manifestation is a collective work by the team from the International Centre for Awqaf Studies (ICAST) of Universitas Darussalam Gontor, chaired by Syahruddin, M.Sc.Fin, with Assoc. Prof. Dr. Khoirul Umam, M.Ec. as the editor. This book comprehensively examines the role of waqf (Islamic endowment) in building and sustaining the educational system and self-sufficiency of Pondok Modern Darussalam Gontor. Through historical, philosophical, and managerial approaches, the book traces the development of Gontor's waqf from the pre-waqf era to its development in the modern era. This book is quite capable of clearly describing the philosophy and manifestation of Gontor's Waqf, covering its historical development, the values that drive it, its management and operational system, and the methods for ensuring its sustainability.